Plan de marketing digital para ropa deportiva masculina Outwod (2024)
This document presents a digital marketing plan for Outwod, a Colombian men's sportswear brand, with the objective of increasing sales tenfold in the next 12 months compared to 2024. Outwod targets active, sports - passionate men aged 25 - 44 who seek function ality, style, and comfort in their athletic wear. The strategy focuses on maximizing social media presence and strengthening customer relationships through valuable content and targeted advertising campaigns. The plan involves developing a detailed social media editorial calendar for platforms like Instagram, WhatsApp, and Mercado Libre, and implementing advertising campaigns on Meta Ads and Mercado Ads. Tools such as Google Analytics and social media analytics will be used to measure the success of action s and adjust strategies in real - time. Outwod offers innovative design, personalized attention, functionality, performance, and a sense of community. The brand targets a male segment with a growing interest in physical well - being and a willingness to invest in quality products. In addition, a referral plan and collaborations with sports accounts are proposed to increase visibility and sales.